Geotechnical properties of clay soil in Alor Setar / Eliyani Yazreen A.Rani - A.Rani, Eliyani Yazreen (Faculty of Civil Engineering, 2006)
This research paper is conducted on geotechnical properties of clay soil at Alor Setar. The main purpose of this study is to obtain design parameters for Alor Setar clay soil. A local database of design parameters characteristics are presented with some empirical or analytical correlation established to estimate SPT value, index properties and mechanical properties of Alor Setar clay. The data are analyzed where the correlation of each parameter with depth are obtained. Conclusions have been made based on the evaluation and the Alor Setar clay are found to have high moisture content, plastic limit, liquid limit and compression index. The soft clay depth is generally down to 8 meter. From the OCR value the clay are indicated as lightly overconsolidated. They are then compared with existing knowledge on Georgetown, Klang, Carey Island and Singapore clay soil. They were found to be in similar range as predicted by Ramli (1999). However, based on Cc value, the compressibilty potential of Alor Setar clay is higher than at other locations. It is hoped that the outcome from this research work can contribute for future reference.